Long-Term Thermal Regimes of Subgrade under a Drainage Channel in High-Altitudinal Permafrost Environment - Hong Yu; Hongwu Han; Wei Ma; Zekun Ding; Ling Chen (Advances in Materials Science and Engineering)
In permafrost regions, construction of a channel involves a large amount of excavation activities and changes to surface water body, which can exert great impacts on the thermal regimes of permafrost underlying. In this paper, a coupled mathematical model of heat and moisture transfer was constructed for freeze-thaw soils to investigate the long-term thermal regimes of subgrade beneath a drainage channel built on the Qinghai-Tibet Plateau. Based on the numerical simulations, the thermal regimes of the subgrade both in warm and cold seasons were analyzed within a period of 50 years, as well as the impact of the widths of the channel. The results showed that the channel excavation and flowing water within could lead to a significant underlying permafrost degradation. During the first 30 years, the permafrost beneath the channel mainly experienced a rapid downward degradation. After that, the lateral thermal erosion of the flowing water led to a rapid permafrost degradation beneath the slope of the channel. In cold seasons, the shallow ground beneath the channel would not refreeze due to the flowing water and the thaw bulb actually expanded throughout the year. For the channel with a bottom width of 15 m, the thaw bulb beneath the channel could expand laterally to the natural ground about 10 m far away from the slope shoulder of channel till the 50th year. With different widths, the long-term thermal regimes of the subgrade beneath the channels differed considerably and the maximum difference was at the slope toe of the embankment. With the numerical simulated results, it is recommended that a channel built on permafrost should be wide-and-shallow rather than narrow-and-deep if conditions permit.